Rural agro-industrial enterprises diversity: typologies of panela production in Huila, Colombia - Polo-Murcia, Sonia Mercedes (2022)
Introduction. Typologies can be used as a mechanism to address the heterogeneity of agricultural systems. Panela, or non-centrifuged cane sugar, is a traditional sweetener of great economic and cultural importance in Colombia, it generates 236,000 direct jobs per year and is produced in 47 % of the country’s municipalities. Objective. To identify typologies of agro-industrial production units (UPA) of panela based on technical and socioeconomic characteristics in the department of Huila, Colombia. Materials and methods. The multivariate statistical technique of mixed data factor analysis (AFDM) was used with data from 94 UPAs, taken from a representative cross-sectional survey of the year 2019 carried out within the framework of this study. The survey provided information on production cycle, socioeconomic, and environmental management management of by-products. Results. Three differentiated types of UPA were identified: type 1(6 UPA- 6.38 %): composed of units oriented to productive diversification and technological transition; type 2 (63 UPA-67.02 %): composed of units with traditional management of the cultivation, processing and use of by-products; and type 3 (25 UPA-26,6 %): composed of units specialized in the production of panela, with greater technification in cultivation and processing of sugarcane. Conclusions. Different heterogeneous groups of panela agro-industrial production units were identified in the department of Huila, Colombia, where a traditional small-scale operation model is developed. The empirical exploration of this research made it possible to delineate the potential for technology adoption in the identified groups. Technology transfer programs should consider the technical and socioeconomic characteristics of the UPAs.